2008
DOI: 10.1097/pep.0b013e31815f1208
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Yoga for Children: A Systematic Review of the Literature

Abstract: The evidence shows physiological benefits of yoga for the pediatric population that may benefit children through the rehabilitation process, but larger clinical trials, including specific measures of quality of life are necessary to provide definitive evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 23 publications
5
133
0
6
Order By: Relevance
“…A systematic review concluded that yoga may have utility for treating anxiety or anxiety-related disorders in child and adolescent populations. 46 The development of self-regulation and coping skills promoted in recreational activities such as yoga and martial arts may explain the positive effects of these activities on mental health. 46,47 …”
Section: Behavioral Mechanismsmentioning
confidence: 99%
“…A systematic review concluded that yoga may have utility for treating anxiety or anxiety-related disorders in child and adolescent populations. 46 The development of self-regulation and coping skills promoted in recreational activities such as yoga and martial arts may explain the positive effects of these activities on mental health. 46,47 …”
Section: Behavioral Mechanismsmentioning
confidence: 99%
“…It can aid the children with attention problems 38 , and also in developing executive function. A group of studies agreed that yoga could help the children with special needs through rehabilitation processes 39 .…”
Section: Figure 5: Standing and Finding The Suitable Balancementioning
confidence: 99%
“…2 Interactive locomotors skills reinforced socialization, which is a goal for many children with autism and other impairments. The cool-down component was necessary for transition back to usual learning activities, a task that is particularly difficult for children with special education needs.…”
Section: Yoga Program Developmentmentioning
confidence: 99%
“…A systematic review by Galantino et al examined 24 studies on the effect of yoga for children and found supporting evidence of positive benefits from yoga in the areas of neuromuscular, musculoskeletal and cardio respiratory physical therapy practice patterns. 2 Serwacki et al+conducted a systematic review of research regarding the effectiveness of yoga based interventions delivered in schools for atypical and typical developing children. They concluded that yoga provided positive results for atypical developing children in the areas of reducing stress, improved self and social confidence, attention and concentration.…”
Section: Introduction Yoga Practice In Schoolsmentioning
confidence: 99%